Evaluasi Unit Instalasi Pengolahan Air (IPA) Miniplant Dago Pakar Perumda Tirtawening Kota Bandung - Niswanurrahim, Zeihan; Sururi, Mohamad Rangga (Jurnal Teknologi Lingkungan Lahan Basah, 2026)
Established in 1986, the Dago Pakar Miniplant is a compact Water Treatment Plant (WTP) operated by Perumda Tirtawening, the municipal water utility of Bandung City, with raw water intake from Pakar Pond and a designed production capacity of 50 liters per second. This study assesses the adequacy of water quantity, the continuity of supply, the quality of both raw and treated water, and the operational performance of the treatment units at the Dago Pakar Miniplant IPA. The findings indicate that the plant currently supplies only 13.7 liters/person/day, which is far below the minimum basic drinking water requirement of 60 liters/person/day stipulated in the Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 71 of 2016. Regarding service continuity, the system is currently operating for 21.91 hours per day, so it has not yet achieved the expected continuous 24-hour operation. Laboratory analysis of raw water shows that 15 parameters, color, BOD₅, COD, DO, nitrite, ammonia, fluoride, free chlorine, iron, manganese, zinc, total detergent, phenol, fecal coliform, and coliform, do not comply with the quality standards specified in Government Regulation Number 22 of 2021. For production (treated) water, three parameters, namely iron, manganese, and residual chlorine, also fail to meet the drinking water quality requirements set out in the Regulation of the Minister of Health of the Republic of Indonesia Number 2 of 2023. These deviations from standard are closely related to several installation units whose condition and configuration are no longer aligned with the original design criteria, ultimately undermining Miniplant Dago Pakar's ability to consistently meet the prescribed standards for water quality, quantity, and continuity.